Relationship of ABO and Rhesus D Blood Group Phenotypes with Type 2 Diabetes Mellitus in Kano, Nigeria - Mukhtar, IG; Bala, AY (Annals of Health Research (Onabanjo University Teaching Hospital), 2024)
Background: ABO and Rhesus D blood group phenotypes have been linked to Type 2 Diabetes mellitus (T2D), but the link has been inconsistent. Objectives: To determine the association between ABO and Rhesus D blood group phenotypes with T2D in Kano, Nigeria. Methods: This case-control study recruited 149 consecutive individuals with Type 2 Diabetes mellitus who presented on four different clinic days and 200 prospective blood donors, using systematic random sampling. ABO and Rhesus D phenotypes were determined using monoclonal antisera. Results: The mean age of the participants was 57 years (26–86 years). ABO phenotypes were significantly associated with T2D (p = 0.001), with frequencies of B and AB phenotypes being higher among T2D patients. The frequency of the A phenotype was lowest among individuals with T2D. Similarly, Rhesus D phenotypes were significantly associated with T2D (p = 0.001), with the frequency of Rh D negative phenotypes being higher among people with T2D. The frequencies of B- (24.07% vs 9.30%), AB- (37.5% vs 00%), and O- (50% vs 6%) phenotypes were significantly higher among T2D patients compared to controls. Compared to O phenotypes, B phenotypes had twice the odds of having T2D (OR = 2.026; 95% CI = 1.215 – 3.376, p = 0.007), while Rhesus D positive phenotypes had 0.14 times the odds of having T2D compared to Rhesus D negatives. Conclusions: Blood group B- and AB- phenotypes are significantly associated with T2D in Kano, Nigeria. More attention should be given to ABO and Rhesus D phenotypes in T2D risk assessment and prevention strategies.